A novel cross‐species inhibitor to study the function of CatSper Ca2+ channels in sperm. (29th June 2018) - Rennhack, Andreas; Schiffer, Christian; Brenker, Christoph; Fridman, Dmitry; Nitao, Elis T; Cheng, Yi‐Min; Tamburrino, Lara; Balbach, Melanie; Stölting, Gabriel; Berger, Thomas K; Kierzek, Michelina; Alvarez, Luis; et al.
Abstract : Background and Purpose: Sperm from many species share the sperm‐specific Ca 2+ channel CatSper that controls the intracellular Ca 2+ concentration and, thereby, the swimming behaviour. A growing body of evidence suggests that the mechanisms controlling the activity of CatSper and its role during fertilization differ among species. A lack of suitable pharmacological tools has hampered the elucidation of the function of CatSper. Known inhibitors of CatSper exhibit considerable side effects and also inhibit Slo3, the principal K + channel of mammalian sperm. The compound RU1968 was reported to suppress Ca 2+ signaling in human sperm by an unknown mechanism. Here, we examined the action of RU1968 on CatSper in sperm from humans, mice, and sea urchins. Experimental Approach: We resynthesized RU1968 and studied its action on sperm from humans, mice, and the sea urchin Arbacia punctulata by Ca 2+ fluorimetry, single‐cell Ca 2+ imaging, electrophysiology, opto‐chemistry, and motility analysis. Key Results: RU1968 inhibited CatSper in sperm from invertebrates and mammals. The compound lacked toxic side effects in human sperm, did not affect mouse Slo3, and inhibited human Slo3 with about 15‐fold lower potency than CatSper. Moreover, in human sperm, RU1968 mimicked CatSper dysfunction and suppressed motility responses evoked by progesterone, an oviductal steroid known to activate CatSper. Finally, RU1968 abolished CatSper‐mediated chemotactic navigation in sea urchin sperm. Conclusion and Implications: We propose RU1968 as a novel tool to elucidate the function of CatSper channels in sperm across species.